Impact of new cancer therapies on outpatient treatment delivery for colorectal cancer: A population‐based study. (20th September 2021) - Chen, Leo; Speers, Caroline H.; Cheung, Winson Y.; Spinelli, John J.; Kennecke, Hagen F.
Abstract: We investigated the impact of new systemic therapies approved in Canada for colorectal cancer on the frequency, intensity and duration of oncology clinic and infusion visits over five treatment phases from diagnosis (P1, P3) to treatment (P2, P4) of primary and metastatic disease, respectively, and during the last 6 months of life (P5). In total, 15, 157 adult patients with newly diagnosed colorectal cancer and referred between 2000 and 2012 to any cancer clinic in British Columbia, Canada, were included. Frequency, intensity and duration of medical oncology clinic visits (CVs), oncology infusions (OIs) and oncology prescriptions (OPs) were measured by treatment phase. Mean, total and adjusted total duration for CVs increased for P1–5. CVs increased in P1–5, and in P1–4 when adjusted by treatment length. Adjusted and unadjusted OIs decreased in P1 coinciding with the introduction of an oral treatment option, but increased in P2–5. Mean OI duration increased in P1–5, while total and adjusted total decreased in P1 and increased in P2–5. OPs increased in P2–4, but were unchanged in P1 and P5. Multi‐fold increases in resources and time required per patient were also observed, which have significant implications for demand projections in cancer care planning and delivery. In conclusion, patients required more visits in almost all treatment phases, visits on average took longer and patients were in treatment for longer periods of time.